STRUKTUR NARATIF MENGENAI KISAH CINTA DIN DAN NUR DALAM PUISI-PUISI KARYA MASYHUDDIN MASYHUDA - I Wayan Nitayadnya (Multilingual, 2013)
The story in the poems Kuala dan Jajaka (1975) by Masyhuddin Masyhuda interrelated with each other. Revealing the narrative unity of the poems and describing the theme, plot, characterization, and settings become the aim of the paper. The method which is applied is literature, analisys descriptive, and narrative arrangement. The analysis result shows that there is a descriptiveunity in poems which has story about love story of Din and Nur. The theme is about Nur’s devotion to Din. The plot is consist of situation, generating circumstances, rising action, and in the end is climax, without the denouement. The main characters are Din and Nur, the second is Nur’s father, and thethird is Nur’s mother, doctor, and dukun (the traditional healer). The main imagery of character is psychological dimension. Social, place, and time setting is used as the setting of the poems.